Evaluation of biomechanical effects of interocclusal surfaces on the mandible - Levrini, Luca; Paracchini, Luigi; Mangano, Carlo; Pisani, Lucia; Caprioglio, Alberto (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: Only few studies in the literature employ a mathematical model in the evaluation of the stress which follows the application of loads and constraints onto the mandible. Therefore, new approaches are needed so that the study of this phenomenoncan rely less on the clinical hypothesis and experience of the operator, while taking advantage of the many benefits that virtual representations and mathematical calculations present. Aim of the study is to determine, by means of the finite element method (FEM), the stress produced onto the mandible as a result of the application of a force on itself, in association or not to the perioralmusculature and according to the dental support given by the positioning of an interocclusal surface at three different levels: mesial, intermediate and distal.Aim: The aim is to allow a more objective evaluation of this phenomenon, its absolute repeatability, as well as to acquire importantclinical informations concerning the role of orthodontic and gnathologic appliances.Materials and methods: Starting from a 1:1 scale model of the mandible (human adult male), a virtual three - dimensional (3D) representation was first obtained thanks to a dedicate software; it was then imported into a second software in order to permit the discretization into finite elements of the virtual model and the attribution of its mechanical properties. Finally, thanks to a specificsoftware, it was possible to simulate the presence of load and constraints and to evaluate the stress status by using pseudo - colors.Results: The stress generated following the application of a force onto the mandible, undergoes significant variations in relation to thedental support and the presence or absence of the perioral musculature.Conclusions: Following the results of our research, we consider FEM as a valid and interesting method for this purpose, however additional FEM conducted studies are necessary in order to assess this phenomenon in more detail and determine the role of the perioral musculature as well as the possible clinical implications.